2018
DOI: 10.3389/fimmu.2018.00464
|View full text |Cite
|
Sign up to set email alerts
|

The Syk-Coupled C-Type Lectin Receptors Dectin-2 and Dectin-3 Are Involved in Paracoccidioides brasiliensis Recognition by Human Plasmacytoid Dendritic Cells

Abstract: Plasmacytoid dendritic cells (pDCs), which have been extensively studied in the context of the immune response to viruses, have recently been implicated in host defense mechanisms against fungal infections. Nevertheless, the involvement of human pDCs during paracoccidioidomycosis (PCM), a fungal infection endemic to Latin America, has been scarcely studied. However, pDCs were found in the cutaneous lesions of PCM patients, and in pulmonary model of murine PCM these cells were shown to control disease severity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 60 publications
2
16
1
Order By: Relevance
“…In immune cells, Dectin-2 is coupled to the Syk kinase, which becomes phosphorylated upon Dectin-2 activation, and further activates the innate immune and host defense responses [41, 42]. In our study, Syk expression in the rumen mucosa and OREC was detected by immunohistochemistry and immunofluorescence, and the localization of Syk in OREC was consistent with that in human bronchial epithelial cells [43].…”
Section: Discussionsupporting
confidence: 76%
“…In immune cells, Dectin-2 is coupled to the Syk kinase, which becomes phosphorylated upon Dectin-2 activation, and further activates the innate immune and host defense responses [41, 42]. In our study, Syk expression in the rumen mucosa and OREC was detected by immunohistochemistry and immunofluorescence, and the localization of Syk in OREC was consistent with that in human bronchial epithelial cells [43].…”
Section: Discussionsupporting
confidence: 76%
“…In contrast to studies in mice, in vitro studies of human plasmacytoid dendritic cells using antibodies to MCL showed that Dectin-2 and Dectin-3 were important [ 110 ]. Dendritic cells ingested P. brasiliensis and inhibited the organism’s growth and this growth inhibition was blocked by anti-Dectin-2 and anti-Dectin-3.…”
Section: Innate Receptors For Pathogenic Fungimentioning
confidence: 99%
“…Dectin-3 may use a signaling pathway similar to those of the other three CLRs to mediate intestinal antifungal immunity. More studies are required to gain more detailed and precise information about its structure and activation [42, 45, 46].…”
Section: Structure and Activation Of Clrsmentioning
confidence: 99%
“…As Dectin-2 recognizes mannans, the mycobiota that Dectin-2 recognizes are C. albicans , Candida glabrata and Cryptococcus neoformans [53]. Dectin-2 can cooperate with Dectin-3 by forming heterodimers to recognize C. albicans [45]. Dectin-2 is also involved in A. fumigatus recognition and its expression is restricted to macrophages [54].…”
Section: Clrs-mediated Immune Recognition Of the Gut Microbiotamentioning
confidence: 99%